Influence of extreme heat events on energy flows in agricultural area with wheat in southern Brazil - Veeck, Gustavo Pujol (2023)
Extreme heat events have been reported more frequently in recent years. However, few studies have addressed the effects of these events on turbulent fluxes in the atmospheric boundary layer. The objective of this study is to investigate the anomalous behavior of sensible and latent heat fluxes and their relationship with extreme heat events in a wheat crop in the municipality of Carazinho-RS during winter. The analysis showed a relationship between the intense advection of warm air from the northern quadrant with the increase of latent heat flux and consecutive days in which the sensible heat flux remains negative. Therefore, the extreme heat event significantly alters the expected pattern for the behavior of near-surface fluxes.